Adoption and ex-post impact of alternative teff production technologies: micro-level evidence from Ethiopia. Issue 3 (2nd July 2020) - Tiruneh, Etsehiwot Semreab; Wassie, Solomon Bizuayehu
ABSTRACT: Using plot-level data from Ethiopia, this study aims to examine the determinants and impact of alternative teff production technologies on the productivity and profitability of smallholder teff producers. The study employed a multinomial endogenous switching regression (MESR) model that accounts for selection bias due to observable and unobservable factors. The authors' results show that technology adoption has a positive association with education, farm size, extension visits, community meetings and asset ownership. On the contrary, distance to input and output markets have a negative and significant effect on the adoption of alternative teff production technologies. The MESR model results reveal that, while full technology adoption is the most productive and profitable option, adopting any of the alternative technologies also substantially improves the productivity and profitability of smallholder teff producers. The results also suggest that row-planting technology has a positive impact on the productivity and profitability of smallholder teff producers only when it is adopted with improved seed technology.